Impact of Mano a Mano‐Mujer, an HIV prevention intervention, on depressive symptoms among Chilean women - R. CIANELLI; L. LARA; N. VILLEGAS; M. BERNALES; L. FERRER; L. KAELBER; N. PERAGALLO (My University, 2012)
Accessible summary Depression is considered a factor that interferes with HIV prevention. Depression may reach 41% among low‐income Chilean women. The current study analyzed the impact of Mano a Mano‐Mujer, an HIV prevention intervention, on depressive symptoms among low‐income Chilean women. Mano a Mano‐Mujer provided significant benefits for women's depression symptoms. AbstractWorldwide, and in Chile, the number of women living with HIV is increasing. Depression is considered a factor that interferes with HIV prevention. Depression may reach 41% among low‐income Chilean women. Depressed people are less willing to participate in behaviours that protect them against HIV. The aim of this study is to analyze the impact of Mano a Mano‐Mujer (MM‐M), and HIV prevention intervention, on depressive symptoms among Chilean women. A quasi‐experimental design was used for this study. The research was conducted in Santiago, Chile; a total of 400 women participated in the study (intervention group, n = 182; control group, n = 218). The intervention was guided by the social‐cognitive model and the primary health care model. The intervention consists of six 2‐h sessions delivered in small groups. Sessions covered: HIV prevention, depression, partner's communication, and substance abuse. Face‐to‐face interviews were conducted at baseline and at 3‐month follow‐up. Chilean women who participated in MM‐M significantly decreased, at 3 months follow up, their reported depressive symptoms. MM‐M provided significant benefits for women's depression symptoms. In this study nurses participated as leaders for the screening of depressive symptoms and as facilitators of community interventions.
Keywords: chile; depression; hiv; aids prevention; nursing; primary care; women